2016
DOI: 10.1002/2015gl067343
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of atypical lateral fire spread to wind and slope

Abstract: This study presents new knowledge of the environmental sensitivity of a dynamic mode of atypical wildland fire spread on steep lee‐facing slopes. This is achieved through a series of idealized numerical simulations performed with the Weather Research and Forecasting (WRF) and WRF‐Fire coupled atmosphere‐fire models. The sensitivity of the atypical lateral fire spread across lee slopes is tested for a varying background wind speed, wind direction relative to the terrain aspect, and lee slope steepness. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 15 publications
(28 reference statements)
2
21
0
Order By: Relevance
“…Figure 2a,b illustrates a schematic of this tilting and stretching process in a nonuniform buoyant velocity field where an eddy-generating mechanism exists. Readers are referred to Sharples et al (2015) and Simpson et al (2016) for theoretical details on the tilting and stretching of vortices during wildland fire scenarios. The converging flow in the vortex column of a fire whirl also concentrates existing vorticity, as shown in Figure 2c.…”
Section: Essential Conditions For Fire Whirl Formationmentioning
confidence: 99%
“…Figure 2a,b illustrates a schematic of this tilting and stretching process in a nonuniform buoyant velocity field where an eddy-generating mechanism exists. Readers are referred to Sharples et al (2015) and Simpson et al (2016) for theoretical details on the tilting and stretching of vortices during wildland fire scenarios. The converging flow in the vortex column of a fire whirl also concentrates existing vorticity, as shown in Figure 2c.…”
Section: Essential Conditions For Fire Whirl Formationmentioning
confidence: 99%
“…Sharples et al (2012) initially expressed these thresholds in terms of a first-order wind-terrain filter, or binary variable χ, which assumes a value of 1 in regions prone to VLS occurrence and 0 elsewhere. While, the first-order filter identified the entire leeward slope as prone to VLS occurrence, subsequent laboratory experiments, wildfire observations and numerical simulations have revealed that the rapid lateral spread associated with VLS really only occurs in a relatively narrow portion of the leeward slope near the top of the hill (Quill and Sharples, 2015;Raposo et al, 2015;Simpson et al, 2016). This region could be better identified using a second-order VLS filter, based on the second-derivative of elevation, but for the idealised cases considered in this paper, a crude approximation will suffice.…”
Section: Vorticity-driven Lateral Spreadmentioning
confidence: 99%
“…This second dependence becomes critical when the spread of a wildfire is dominated by the dynamic modes of fire propagation, which arise in response to multi-scale interactions between the fire and the local atmosphere. Examples of these dynamic modes of fire propagation include eruptive fire spread (Viegas, 2006;Viegas and Pita, 2004) and vorticity-driven lateral spread (Sharples et al, 2012;Simpson et al, 2013Simpson et al, , 2014Simpson et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 10 years, many studies have investigated the formation and impacts of pyroconvective processes and pyrocumulonimbus events (Fromm et al 2006(Fromm et al , 2008a(Fromm et al ,b, 2010Peterson et al, 2015Peterson et al, , 2017Dowdy et al 2017). Plume dynamics and wind modification are well known as a major source of uncertainty for modelling bushfire spread, and in particular knowledge gaps relating to coupled fire-atmospheric dynamics including the occurrence and growth of pyrocumulus (pyroCu) and pyrocumulonimbus (pyroCb) events (Peace et al 2011;Potter 2012;Simpson et al 2016). Despite the recent attention pyroCb cloud has received, little research has been able to relate the formation of pyroCu or pyroCb to wind field characteristics at the surface and aloft in observations (McRae et al 2015).…”
Section: Introduction and Summary Of Previous Studiesmentioning
confidence: 99%